E. P. con Hugo Calligaris : [interview]. - Peicovich, Esteban (Colección Los Palabristas, 2007)
Esteban Peicovich reads a text by journalist Francisco Umbral. Peicovich interviews journalist Hugo Caligaris. Caligaris grew up in Boedo, Buenos Aires, Argentina, where he currently resides. He worked as a parliamentary reporter for La Nacion 1983-1989 and was head of the Sunday paper for La Nacion. Caligaris has authored Las palabras: Dictionario de disparates politicos, a recompilation of articles he has written. Peicovich reads a segment of the prologue to La palabra. Caligaris talks about his heritage and his initial passion for writing. Peicovich reads a brief text by Jorge Blanco Villegas and the dedication of Caligari's work. Caligaris and Peicovich discuss a journalist's writing approach. Caligaris tells where he believes the future of newspapers is headed and its need to report good news.